In Vitro Antibacterial Activity of Metformin Against Gram-Positive and Gram-Negative Bacteria Associated with Diabetic Wounds - Melis Esma Demirbilek; Kaan Zıkşahna; Yağmur Ekenoğlu Merdan (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
Objective: This study aimed to determine the in vitro antibacterial activity of metformin hydrochloride against reference strains of Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, and Enterococcus faecalis associated with diabetic wound infections.Methods: P. aeruginosa ATCC 27853, S. aureus ATCC 25923, E. coli ATCC 25922, and E. faecalis ATCC 29212 were used. The antibacterial activity of metformin hydrochloride was evaluated using agar well diffusion and broth microdilution methods. Minimum bactericidal concentrations were determined by subculturing samples from wells without visible bacterial growth onto Mueller–Hinton agar. The experiments were performed in three technical replicates.Results: No measurable inhibition zone was observed for any of the tested strains in the agar well diffusion assay. The minimum inhibitory concentration was 64 mg/mL for P. aeruginosa, S. aureus, and E. coli and 128 mg/mL for E. faecalis. The minimum bactericidal concentration was 128 mg/mL for P. aeruginosa and E. coli and greater than 128 mg/mL for S. aureus and E. faecalis.Conclusion: Metformin hydrochloride exhibited species-dependent antibacterial activity. A bactericidal endpoint was achieved for P. aeruginosa and E. coli, whereas no definitive bactericidal endpoint was reached for the Gram-positive strains within the tested concentration range. These findings demonstrate that the antibacterial activity of metformin may vary according to the evaluation method and provide preliminary data for investigating its potential in local or controlled-release systems.